Dielectric and Excess Dielectric Constants of Acetonitrile + Butyl Amine, + Ethylamine, and + Methylamine at 303, 313, and 323 K - Ch. V. V. Ramana; A. B. V. Kiran Kumar; M. Ashok Kumar; M. K. Moodley (Journal of Chemistry)
The dielectric constants and excess dielectric constants of the binary systems: acetonitrile + butyl amine, + ethylamine and + methylamine have been studied at 303, 313, and 323 K temperatures and over the complete mole fraction range. The dielectric constants for these mixtures were measured using a microcontroller based system. The results are positive over the entire range of composition. Symmetrical curves were observed for the systems in which the maximum occurs approximately at 0.7-mole fraction of acetonitrile. The results are discussed in terms of intermolecular interactions. The investigation of dielectric constant of mixed solvents bearing amines aims at better comprehension of their biological, chemical, pharmaceutical, technological, and laboratory applications.